Sosialisasi Penggunaan Aplikasi Canva dalam Penulisan Buku Ajar Bagi Tenaga Pengajar di Rumah Belajar PATMOS : Pengabdian - Lois Oinike Tambunan; Janwar Tambunan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity aims to train the teaching staff at PATMOS Learning Center in the process of creating teaching materials, which will later be used at the learning center, by utilizing the Canva application. The socialization was carried out using a presentation and interaction method, where the 15 teaching staff participants gave positive feedback during the activity. The presentation was conducted by displaying and explaining how to use the Canva application through a PowerPoint presentation and by directly demonstrating it on the Canva website. Through the interactions, it was revealed that some participants had never used Canva before, making this socialization very beneficial for the teaching staff at the learning center, as seen from the participants' enthusiasm throughout the event. The Community Service team also hopes that in the future, there will be further training for the teaching staff to better understand how to use the Canva application and assist in the process of creating teaching materials.